Functional State Hardware Evaluation System in Educational Medium - Evgeny, N. Moos; Elena, V. Moos (Journal of Current Scientific Research, 2022)
Diagnosis of heart rate variability as an indicator of the impact of external and internal media can serve to make changes in the educational environment. The approach to the organization of the educational process is developed on the basis of quantitative indicators of the students’ functional state using the hardware-software complex " Varikard ".
Keywords: Heart rate variability; educational environment; hardware-software complex Varikard